Appraisal of Indigenous Interview Programme Presentation: A Study of Masoyinbo (Journal of Management and Social Sciences, 2026)
Television interview programmes involve the use of various presentation styles that make the conversation appealing to the audience, but indigenous style has proved to be very unique. This study examined the use of indigenous style on Masoyinbo programme presentation which featured selected Nigerian celebrities with focus on promoting Yoruba language by means of presentation style combining interactive question and answer pattern, contextual clues, and funny engagement to improve guests' knowledge while maintaining audience entertainment. Development Media Theory was adopted in line with postulation which advocated for the use of media to foster the socio-cultural, economic, and political development of society, aligning with the promotion of indigenous media for development purposes. Qualitative content analysis method was used to purposively select 6 episodes of the Masoyinbo programme that were transmitted both on African magic Yoruba and streamed on social media of YouTube covering six months duration between October, 2024 to March, 2025. The data analysis revealed the presenter's adoption of professional techniques on indigenous presentation style combining interactive teaching, humor, and cultural references especially in the episodes investigated. The study concluded that aside critical interview style used in television interviews, Masoyinbo indigenous style allowed for transmission of Yoruba cultural values to the audience. While the paper recommended that Masoyinbo programme should include live audience participation or viewer submitted questions to increase involvement and create a more communal learning experience, visual aids like on-screen Yoruba spellings or brief clips/videos showing word use would help both guests and viewers learn as well.KeywordsTelevision interview, programmes, presentation styles, indigenous, Masoyinbo, cultural values